2015
DOI: 10.1002/jwmg.955
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity among subpopulations of louisiana black bears as estimated by a step selection function

Abstract: Habitat fragmentation is a fundamental cause of population decline and increased risk of extinction for many wildlife species; animals with large home ranges and small population sizes are particularly sensitive. The Louisiana black bear (Ursus americanus luteolus) exists only in small, isolated subpopulations as a result of land clearing for agriculture, but the relative potential for inter-subpopulation movement by Louisiana black bears has not been quantified, nor have characteristics of effective travel ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Total distances of predicted paths in the central region range from approximately 135 to 210 km, whereas paths in the western periphery may exceed 350 km. In fact, results of a first attempt to model movement between the populations support this notion: Based on the SSF we reported here, we initially used a correlated random-walk method similar to Clark et al (2015). To date, the most remote verified observations of grizzly bears within the region between the populations were located~110 km from the GYE and~95 km from the NCDE (locations 9, 10, 11, and 17), confirming that movements within this distance range are possible (Table 3).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Total distances of predicted paths in the central region range from approximately 135 to 210 km, whereas paths in the western periphery may exceed 350 km. In fact, results of a first attempt to model movement between the populations support this notion: Based on the SSF we reported here, we initially used a correlated random-walk method similar to Clark et al (2015). To date, the most remote verified observations of grizzly bears within the region between the populations were located~110 km from the GYE and~95 km from the NCDE (locations 9, 10, 11, and 17), confirming that movements within this distance range are possible (Table 3).…”
Section: Discussionmentioning
confidence: 78%
“…The randomized shortest path (RSP) algorithm, introduced to the field of movement ecology by Panzacchi et al (2016), is a new methodological approach to predict the location of paths between functional areas based on step-selection functions (SSF) derived from individual-based movement data. By modulating the degree of randomness in simulated movements, the algorithm has the potential to better capture the movement ecology of species compared with optimal least-cost path (Walker andCraighead 1997, Cushman et al 2009) or random-walk approaches (Clark et al 2015). This approach was particularly appropriate for our objective to delineate potential paths for gene flow between the GYE and NCDE populations.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Hooker (), Lowe (), and Troxler () estimated bear abundances at the Tensas River Basin (TRB), Upper Atchafalaya River Basin (UARB), and Lower Atchafalaya River Basin (LARB), respectively. Additionally, O'Connell‐Goode et al () updated population estimates and evaluated the effects of flooding the Morganza Spillway on bear demographics at UARB and Clark et al () assessed movement characteristics within and connectivity among Louisiana black bear subpopulations in Louisiana.…”
Section: Introductionmentioning
confidence: 99%
“…A population genetic structure analysis indicated that no immigration into the Spillway from the other 3 Louisiana black bear populations has occurred (S. M. Murphy, Louisiana Department of Wildlife and Fisheries, unpublished data). Furthermore, a step‐selection function analysis of global positioning system (GPS) telemetry data on bears in Louisiana indicates that the potential for such movement is low (Clark et al ). Therefore, we conclude that most of the estimated f are likely from births that occurred within the Upper Atchafalaya population.…”
Section: Discussionmentioning
confidence: 99%
“…O'Connell-Goode et al (2014) reported that w was unaffected by the flood; to test that Table 1. Results from robust-design Pradel models using noninvasive capture-mark-recapture hair trapping data of Louisiana black bears in the Spillway portion of the Upper Atchafalaya River Basin, Louisiana, USA, 2007-2015 We modeled apparent survival (w) as constant (.) and as a function of a sex and year interaction (sex  yr); per capita recruitment (f) by year, sex, and the lack of recruitment of yearlings and 2-year-olds following the 2011 flood event whereby f(6) and f(7) ¼ f for 2012-2013 and 2013-2014, respectively; proportion of the population belonging to 1 of 2 heterogeneity mixtures (p); probability of capture (p) as a function of flood, sex, year, and mixture (mix); and probability of recapture (c) as a behavioral response (add) or independent.…”
Section: Discussionmentioning
confidence: 99%